MITIGASI NON STRUKTURAL BENCANA KEBAKARAN BERBASIS KAWASAN WISATA DAN PERMUKIMAN PADAT PENDUDUK (Studi Kasus Di Kampung Pelangi Kota Semarang) - Verlina Intan Wulandari; Suroto Suroto; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Semarang City has many tourism destination, one of it is Kampung Pelangi with terracing pattern. This destination located in densely populated area, between one houses with another coincided due to the increasing house demand while the existing land is limited. There is Kelurahan Tangguh Bencana (Katana) but its role has not been optimal due to limited funding constraints. Simulation of fires involving residents has never been held in Kampung Pelangi.This causes the Kampung Pelangi prone to fire disasters. The purpose of this study is to analyze the non structural mitigation of fire disasters based on tourism and densely populated area in Kampung Pelangi RW III and IV Village of Randusari, South Semarang Subdistrict, Semarang City. This research is a descriptive with qualitative approach. Sampling using purposive sampling. Five key informants and six triangulation informants. Instruments in this study using indepth interview guides and observation sheets.The result of the research shows that all informants have good knowledge and attitude about fire, socialization and fire training has been held twice in a year with representative participants from community leaders and administrators of Kelurahan Tangguh Bencana (Katana) while the appeal to the citizens is delivered during meeting in RT, there is no specific budget for disaster funds, Local Regulation No. 13/2010 is only known by community leaders, Katana program is not optimal because limited funding, all key informants have reminded their families to prevent fire, RT / RW also gives direct appeal to the citizens, there are rules about trash management in Kampung Pelangi, many tourism attraction need to be developed by applying Occupational Safety and Health (OSH) aspects. Non structural mitigation of fire disaster can increase awareness of local citizens and to secure safety for the visitors Kampung Pelangi.